Identification of CCCH Zinc Finger Proteins Family in Moso Bamboo (Phyllostachys edulis), and PeC3H74 Confers Drought Tolerance to Transgenic Plants - Chen, Feng; Liu, Huan-Long; Wang, Kang; Gao, Ya-Meng; Wu, Min; Xiang, Yan (Frontiers in Plant Science, 2020)
CCCH zinc finger proteins are a class of important zinc-finger transcription factors and have functions in various plant growth and stress responses, but their functions in moso bamboo (Phyllostachys edulis) are unclear. In this current study, we main investigated the structures, phylogenetic relationships, promoter elements and microsynteny of PeC3Hs. In this research, 119 CCCH zinc finger proteins (PeC3H1- 119) identified genes in moso bamboo were divided into 13 subfamilies (A- M) based on phylogenetic analysis. Meanwhile, moso bamboo were treated with abscisic acid (ABA), methyl jasmonate (Me-JA) and gibberellic acid (GA) and 12 CCCH genes expression levels were assayed using qRT-PCR. In the three hormone treatments, 12 genes were up-regulated or down-regulated respectively. In addition, PeC3H74 was localized on the cytomembrane, and it had self-activation activities. Phenotypic and physiological analysis showed that PeC3H74 (PeC3H74-OE) conferred drought tolerance of transgenic Arabidopsis, including H2O2 content, survival rate, electrolyte leakage as well as malondialdehyde content. Additionally, compared with wild-type plants, transgenic Arabidopsis thaliana seedling roots growth developed better under 10 μM ABA; Moreover, the stomatal of over-expressing PeC3H74 in Arabidopsis changed significantly under ABA treatment. The above results suggest that PeC3H74 was quickly screened by bioinformatics, and it may enhanced drought tolerance in plants through the ABA-dependent signaling pathway.